The son [compact disc, unabridged] : a novel - Nesbø, Jo, 1960- (Random House Audio, 2014)
The author of the best-selling Harry Hole series now gives us an electrifying stand-alone novel set inside Oslo's maze of especially venal, high-level corruption.